Beyond Traditional Methods : How Online Whiteboarding Transforms Learning, Collaboration, and Engagement - Zhen Wei, Goh; Agatha Lamentan, Muda (UNIMAS Publisher, 2024)
This study explored the effect of online or digital whiteboarding on students' academic experiences to evaluate its efficacy, contribution to promoting collaboration, and effect on retention and engagement. Analysis of questionnaire responses from 51 students revealed how Padlet has diverse and significant influences on educational environments. Specifically, the tool demonstrated considerable potential in enhancing students' understanding of subjects, surpassing traditional learning methods. Furthermore, its use significantly improved student teamwork and communication, proving an effective collaboration tool in learning sessions. Finally, Padlet positively affected concept recall, improving overall engagement and satisfaction with the learning process. This study underscores the significant benefits of incorporating online whiteboarding tools like Padlet into the instructional environment. It highlights how Padlet enhances learning experiences, fosters collaboration, and increases student satisfaction with learning. Thus, the study advocates for integrating Padlet as a novel technological solution to enrich education and provide students with a more interactive and efficient learning environment.